PENGGARUH MODEL PEMBELAJARAN JIGSAW TERHADAP HASIL BELAJAR STUDI MASYARAKAT INDONESIA MAHASISWA - Siti Suprihatin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
The aims of the study is to determine the effect of jigsaw learning model on the learning outcomes of the Indonesian society study at the second semester of the economy education in the academic year of 2016/2017.  The population in this study were 47 students consisting of 2 classes, A class and B class. The sample in this study is A class of 26 students and B class of 21 students. Sampling technique in this research is using Pusposive Sampling with certain consideration reason. Based on the results of simple linear regression analysis conducted by the researchers obtained the results at the level of significance α = 0.05 yield tcount = 8.97 and ttable = 2.020 which means thitung> ttable so H0 rejected and H1 accepted, thus it can be concluded that there is significant influence of jigsaw learning model on the learning outcomes of the Indonesian society study at the second semester of the economy education in the academic year of 2016/2017. Keywords: Learning Outcomes, Jigsaw, Learning Model